The motivation behind unsanctioned violence in international rugby: A case study of a former elite player - Kerr, J. H. (International Journal of Sport and Exercise Psychology, 2017)
At focus in this case study was the participant's perception of, and personal involvement in, rugby violence. The participant was a 50-year-old ex-international and former British and Irish Lions rugby union player. A qualitative approach informed by reversal theory and incorporating retrospective semi-structured interview procedures with inductive and deductive elements was used to explore a number of topics related to his rugby playing career, including rugby violence. Among other statements related to play and power violence, the participant described his experience of three major incidents involving personal rugby violence. Each incident resulted in injury to the opposing player which required extensive medical attention. Two of the reported incidents supported previous reversal theory-based research findings related to the motivation behind anger violence in sport. The third incident illustrated a type of sport violence not previously identified in reversal theory-based sport research. It was termed "protective" or "supportive" violence, where an athlete comes to the aid, rescue or defence of a teammate. The findings provide valuable new insights on rugby violence, adding to sport psychology's understanding of the motivational processes involved.